Prevalence of pain in adult patients Pain prevalence - Çınar, Fadime; Eti Aslan, Fatma; Yalın, Hayat; İlbey Koç, Betül; Hacıdursunoğlu Erbaş, Dilay; Özdemir Aslan, Emine (BAYRAKOL MEDICAL PUBLISHER, 2021)
Aim: This study aimed to determine the frequency and characteristics of pain in inpatients. Material and Methods: This study was conducted as an analytical and cross-sectional type of time prevalence on 25-26-29-30 July 2019, including 127 patients hospitalized in a public hospital in Istanbul. Data were collected through the Introductory Information Form, the Brief Pain Inventory (BPI), and the Revised American Pain Society Patient Results Questionnaire through face-to-face interviews. The mean, percentage distribution and standard deviation values were calculated using descriptive statistical methods. First of all, the Kolmogorov-Smirnov, Shapiro Wilk-W tests were performed and the normal distribution of the data was examined. According to these results, nonparametric tests were applied. The Mann-Whitney U test was used between two independent groups, the Kruskal-Wallis test and Spearman’s Correlation analysis were used between more than two independent groups. Results: As a result of the analysis of the obtained data, the average age of the participants included in the study was 48.13 ± 16.88 years. In addition, it was found that maximum 37% (n = 47) were primary school graduates and 53.5% (n = 68) were women. It was determined that 44.9% (n = 57) of the participants preferred most digestive system and surgical diseases as medical diagnosis and treatment, and 59.8% (n = 76) preferred paracetamol as analgesic use. It was determined that 21.3% (n = 27) of the pain they experienced was a stinging type. It was found that the most pain was felt in the abdomen and pelvic region in 56.7% (n = 72). The Brief Pain Inventory total score average was 5.80 ± 1.85 and the pain prevalence was 76.37%. Discussion: The prevalence of pain in adult patients in Turkey, according to the survey results, is quite high. Despite the high prevalence of pain, moderate pain intensity may be associated with ethnic and socioeconomic factors in the perception of pain. It is recommended that health professionals who play an important role in relieving or eliminating pain, increase their knowledge of pain, and coping with pain
Keywords: Pain; Adults; Prevalence; Turkey